Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1172/jci34057
|View full text |Cite
|
Sign up to set email alerts
|

The E1784K mutation in SCN5A is associated with mixed clinical phenotype of type 3 long QT syndrome

Abstract: Phenotypic overlap of type 3 long QT syndrome (LQT3) with Brugada syndrome (BrS) is observed in some carriers of mutations in the Na channel SCN5A. While this overlap is important for patient management, the clinical features, prevalence, and mechanisms underlying such overlap have not been fully elucidated. To investigate the basis for this overlap, we genotyped a cohort of 44 LQT3 families of multiple ethnicities from 7 referral centers and found a high prevalence of the E1784K mutation in SCN5A. Of 41 E1784… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
200
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 149 publications
(209 citation statements)
references
References 42 publications
(74 reference statements)
7
200
1
1
Order By: Relevance
“…The genetic analysis identified an E1784K mutation in SCN5A ( Figure 1C, Table), the prevalent SCN5A mutation in both type 3 long QT syndrome (LQT3) and BrS. 12,17,18) Patient B29, a 25-year-old male patient, had an episode of syncope. A saddle-back ST elevation in the precordial lead was present in an ECG ( Figure 1D), but a drug provocation test was not performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic analysis identified an E1784K mutation in SCN5A ( Figure 1C, Table), the prevalent SCN5A mutation in both type 3 long QT syndrome (LQT3) and BrS. 12,17,18) Patient B29, a 25-year-old male patient, had an episode of syncope. A saddle-back ST elevation in the precordial lead was present in an ECG ( Figure 1D), but a drug provocation test was not performed.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of SCN5A mutations is not related to the severity of the disease. 9,10,12) However, Meregalli, et al have recently reported that the type of SCN5A mutation in BrS1 in European countries may determine the clinical severity. 13) Because the clinical features of BrS vary among different ethnicities, 14,15) it is of great value to investigate the genotype-phenotype relationship of BrS in Asians in whom the ratio of BrS patients is relatively high compared to subjects from different ethnic backgrounds.…”
mentioning
confidence: 99%
“…The following conditions, which can account for the ECG changes and syncope, should be excluded: atypical right bundle branch block; left ventricular hypertrophy; early repolarization; acute pericarditis; acute myocardial ischemia or infarction; pulmonary embolism; Printzmetal angina; dissecting aortic aneurysm; central or peripheral nervous system abnormalities; Duchenne muscular dystrophy; thiamine deficiency; hyperkalemia; hypercalcemia; arrhythmogenic right ventricular cardiomyopathy; pectus excavatum; hypothermia, or mechanical compression of the right outflow tract (RVOT) as seen with mediastinal tumors or hemopericardium. Adapted from the 2005 consensus paper [Antzelevitch et al, 2007], BrS with conduction disease (CCD) [Rossenbacker et al, 2004], BrS with LQTS, CCD, and dilated cardiomyopathy (DCM) and combinations thereof, have been described elsewhere [Makita et al, 2008;Olson et al, 2005].…”
Section: Pathogenetic Mechanism-in Overviewmentioning
confidence: 99%
“…In the clinical sudden infant and adult death syndromes (SIDS and SADS), mutations are also found in SCN5A Behr et al, 2008;Wang et al, 2007]. Mixed phenotypes, where SCN5A mutations are associated with a combination of hereditary arrhythmias and structural heart disease, have also been described [Makita et al, 2008;Olson et al, 2005;Rossenbacker et al, 2004].…”
Section: Brs1-mutations In Scn5amentioning
confidence: 99%
“…85 Conversely, although gain-of-function SCN5A mutations are found in LQT3, an overlap in phenotype exists between BrS and LQTS, both having been described in large families. 67 In addition, there are large SCN5A positive families that have affected individuals who are noncarriers, suggesting a modifier role rather than direct causation in these pedigrees. 86 Many other genes have been associated with the syndrome (Table I).…”
Section: Causes Of Sads and The Role Of Genetic Testingmentioning
confidence: 99%